Corrosion studies on post-weld heat treated dissimilar AISI 2205 and AISI 310 joints using electrochemical noise analysis - Govindasamy, Mahadevan (Strojniški vestnik, 2025)
The corrosion behavior of dissimilar weldments between AISI310 and AISI2205 stainless steels in a 5 % calcium chloride solution at 50 °C was investigated under three conditions: as-welded, lower post-weld heat treatment at 800 °C, and higher post-weld heat treatment at 1000 °C. Microstructural examination revealed severe pitting in the as-welded sample, with pit widths ranging from 270 µm to 360 µm. The lower heat-treated sample had larger pits (310 µm to 370 µm), while the higher heat-treated sample showed homogeneous corrosion with a protective oxide coating. The as-welded sample had the highest corrosion rate, followed by the lower heat-treated sample, which had a moderate rate, and the higher heat-treated sample had the lowest rate. The corrosion current densities were 5,26 × ?$10^{-3}$? mA/cm2, 4,6 × ?$10^{-4}$? mA/cm2 and 1,4 × ?$10^{-4}$? mA/cm2, respectively. Electrochemical noise measurements confirmed these findings, with the higher heat-treated sample showing negligible localized corrosion and homogenous corrosion behavior.
Keywords: AISI2205; Ca?$Cl_2$?; corrosion; electrochemical impedance spectroscopy